A model for selection and evaluation of investment alternatives in dairy cattle - Wolfart, Simone Beatriz; Elejalde, Denise Adelaide Gomes; Bortoluzzi, Sandro César; de Lima, José Donizetti (Frontiers in Sustainable Food Systems, 2025)
In rural areas, continuous changes require managers to seek technologies to improve the property’s sustainability. Thus, the present research aimed to develop a constructivist multi-criteria model for the choice of Investment Alternatives (IA) in dairy cattle for subsequent economic-financial evaluation in a rural property in Brazil. It is a case study, characterized by nature as applied, and of a descriptive character, with a qualitative and quantitative approach. The intervention instrument called Methodology Multicriteria Decision Aid Constructivist (MCDA-C) was used to develop the IA choice model for dairy cattle. Subsequently, the best IA was submitted to the economic-financial appraisal through a framework, which guided the choice of the investment evaluation methodology. The framework integrates the Expanded Multi-Index Methodology (EMIM) for deterministic situations, the Monte Carlo Simulation (MCS) in the presence of uncertainty, and the Real Options Analysis (ROA) in the existence of relevant managerial flexibilities. The main results of the MCDA-C for the choice of IA in dairy cattle was the identification of 22 Primary Assessment Elements (PAEs), which generated 29 concepts (objectives), divided into 4 Fundamental Points of View (FPV): profitability; sustainability; quality; and productivity, which unfolded in elementary points of view and the construction of 17 descriptors with ordinal and cardinal scales of measurement. Verifying the status quo made it possible to conduct global assessment of each IA. The best alternative (A3, formed by the free stall, milking robotization, and photovoltaic systems projects) reached 99.38 points, considered competitive, on a scale where 0 points (neutral level) and 100 points (good level). Next, the investment via EMIM was evaluated, which showed that this alternative has an expected return of a medium degree and a high level of sensitivity, indicating the need to use the MCS. Thus, 100,000 pseudo-random simulations were performed, indicating a low probability of financial failure in implementing A3. The research contributes to filling the gaps identified in the literature, as it integrates an MCDA-C for the choice of IA with the respective economic-financial viability analysis. It is worth mentioning that the theoretical-methodological proposal of the present study can be applied to other rural properties.